Effect of LED curing on the marginal leakage of a pit and fissure sealant - Pineda Mejia, Martha Elena (2013)
The purpose of this study was to evaluate in vitro the curing effect of a light-emitting diode LED unit and conventional halogen light on the marginal leakage of a pit and fissure sealant. We used 40 caries-free permanent premolars recently extracted, which were randomly divided into two groups (n = 20), sealed with a resin based fissure sealant, Helioseal F (Ivoclar Vivadent), according to the manufacturer patterns, then photopolymerized using either L.E.D. light or conventional halogen light (control group). The specimens were stored in distilled water at 37 ° C for 48 hours, and covered all tooth surfaces with nail enamel except for a margin of 2 mm around the sealants, the samples were then immersed in a 1% blue methylene dye solution as a marginal leakage indicator, and subjected to thermocycling regimen of 500 cycles between 5 °C and 60 °C. After removal of the dye solution specimens were sectioned lingual to vestibule way, to evaluated marginal leakage on a stereomicroscope. 35% and 60% of the sealants photopolymerized using either L.E.D. light or conventional halogen light showed some degree of marginal leakage, but the difference was not statistically significant (p> .05). The curing L.E.D. light or conventional halogen light has similar effects on the marginal leakage degree of a pit and fissure sealant.